Pendampingan Kelompok Masyarakat Akibat Erupsi Gunung Sinabung Dalam Menciptakan Ekonomi Kreatif Di Desa Sigarang- Garang, Kecamatan Naman Teran, Kabupaten Karo - Sinta Diana Martaulina; Selvie Sianipar; Riodinar Harianja; Lamhot; Tonggo Sangap Timbul Girsang (Cattleya Darmaya Fortuna, 2024)
Sigarang-garang village is one of the hardest hit villages by the eruption of Mount Sinabung, in Karo district, North Sumatra province. Almost fourteen years ago (2010-now 2024), a torrent of volcanic ash and hot lava enveloped Sigarang-garang village, leaving it in ruins. Sigarang-garang village is one of the red zone areas, meaning it is still a dangerous area to live in. Sigarang-Garang is a village location that has a suitable climate for agricultural land, especially vegetable crops which are the village commodity. The natural beauty around the village near the tourist spot of Lake Lau Kawar is a community group development program in areas affected by natural disasters. Lava eruptions accompanied by large stone spew (batu mbelin) also have economic value that can improve the village economy. One of the village programs being designed is to improve the condition of the village, such as rearranging village infrastructure, population settlements, remapping agricultural land and other things to restore the wheels of life in Sigarang-garang Village. The model for assisting community groups in Sigarang-garang Village, Naman Teran District in managing the environment and biodiversity as local natural resources is to create a village creative economy. The strategies carried out include contributing knowledge about the creative economy in Sigarang-garang Village, Naman Teran District. Empowering the community in Sigarang-garang Village, Naman Teran District in utilizing the environment and biodiversity to create a creative economy. This program is continued by developing the natural potential in Sigarang-garang Village, Naman Teran District as an asset in creating a creative economy.